2018
DOI: 10.3171/2018.2.peds17713
|View full text |Cite
|
Sign up to set email alerts
|

Complication rates for preexisting baclofen pumps and ventricular shunts following scoliosis correction: a preliminary study

Abstract: OBJECTIVEMany patients undergoing spinal fusion for neuromuscular scoliosis have preexisting neurosurgical implants, including ventricular shunts (VSs) for hydrocephalus and baclofen pumps (BPs) for spastic cerebral palsy. Recent studies have discussed a possible increase in implant complication rates following spinal fusion, but published data are inconclusive. The authors therefore, sought to investigate: 1) the rate of implant complications following fusion, 2) pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…To our knowledge, few studies [27][28][29][30][31][32][33] have reported complications in patients undergoing baclofen pump implantation and spine surgery, and no studies have focused on GF procedures. We found no significant difference in rates of unplanned surgical intervention between the pump and control groups, consistent with the findings of Dallas et al 29 for spinal fusion. We also demonstrated that postoperative complications remain an important consideration when the pump is inserted before, during, or after the initial GF spine surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, few studies [27][28][29][30][31][32][33] have reported complications in patients undergoing baclofen pump implantation and spine surgery, and no studies have focused on GF procedures. We found no significant difference in rates of unplanned surgical intervention between the pump and control groups, consistent with the findings of Dallas et al 29 for spinal fusion. We also demonstrated that postoperative complications remain an important consideration when the pump is inserted before, during, or after the initial GF spine surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Further, we found no significant difference in the odds of mechanical complications during the follow-up period for patients with versus without pumps. Although previous studies have addressed baclofen pump device complications for patients undergoing both spinal deformity correction and pump insertion, [27][28][29]31 to our knowledge, ours is the first study to address postoperative mechanical complications related to spinal instrumentation in this population. It should be noted that age at surgery and specific diagnosis are not associated with mechanical complications after surgical correction in patients with neuromuscular scoliosis, thereby supporting the lack of difference between our 2 study groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study suggested that spinal fusion for neuromuscular scoliosis correction does not increase the rates of complications involving previously placed neurosurgical implants. 58…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
“…Many patients undergoing spinal fusion for neuromuscular scoliosis have preexisting neurosurgical implants, including ventricular shunts for hydrocephalus or baclofen pumps for spasticity control. A recent study suggested that spinal fusion for neuromuscular scoliosis correction does not increase the rates of complications involving previously placed neurosurgical implants [ 59 ].…”
Section: Outcomes and Complications After Surgerymentioning
confidence: 99%